Fatigue Design of Marine Structures - Lotsberg, Inge (Cambridge University Press, 2016)
Fatigue Design of Marine Structures provides students and professionals with a theoretical and practical background for fatigue design of marine structures including sailing ships, offshore structures for oil and gas production, and other welded structures subject to dynamic loading such as wind turbine structures. Industry expert Inge Lotsberg brings more than forty years of experience in design and standards-setting to this comprehensive guide to the basics of fatigue design of welded structures. Topics covered include laboratory testing, S-N data, different materials, different environments, stress concentrations, residual stresses, acceptance criteria, non-destructive testing, improvement methods, probability of failure, bolted connections, grouted connections, and fracture mechanics. Featuring 20 chapters, 300 diagrams, 47 example calculations, and resources for further study, Fatigue Design of Marine Structures is intended as the complete reference work for study and practice.